Reproductive and Developmental Toxicity Assessment of Human Umbilical Cord Mesenchymal Stem Cells in Rats - Li, Xiaobo; Huang, Qijing; Zhang, Xiangxiang; Xie, Changfeng; Liu, Muyun; Yuan, Yueming; Feng, Jianjia; Xing, Haoyu; Ru, Li; Yuan, Zheng; Xu, Zhiyong; Yang, YaoXiang; et al. (Frontiers in Cell and Developmental Biology, 2022)
Objective: Human umbilical cord mesenchymal stem cells (hUC-MSCs) have shown very attractive potential in clinical applications for the treatment of various diseases. However, the data about the reproductive and developmental toxicity of hUC-MSCs remains insufficient. Thus, we assessed the potential effects of intravenous injection of hUC-MSCs on reproduction and development in Sprague-Dawley rats. Methods: In the fertility and early embryonic development study, hUC-MSCs was administered at dose levels of 0, 6.0×106, 8.5×106 and 1.2×107/kg to male and female rats during the pre-mating, mating and gestation period. In the embryo-fetal development study, the pregnant female rats received 0, 0.6×107, 1.2×107 and 2.4×107/kg of hUC-MSCs from gestation days (GD) 6 to 15. Assessments made included mortality, clinical observations, body weight, food consumption, fertility parameters of male and female, litter and fetus parameters, etc. Results: No hUC-MSCs-related toxicities was observed on the fertility of male and female rats, and no teratogenic effect on fetuses. hUC-MSCs at 1.2×107/kg caused mildly decrease in body weight gain of male rats, transient listlessness, tachypnea and hematuria symptoms in pregnant female rats. Death was observed in part of the pregnant females at a dose of 2.4×107/kg, which could due to pulmonary embolism. Conclusion: Based on the results of the studies, the no-observed-adverse-effect levels (NOAELs) are 8.5×106/kg for fertility and early embryonic development, 1.2×107/kg for maternal toxicity and 2.4×107/kg for embryo-fetal development in rats intravenous injected with hUC-MSCs, which are equivalent to 8.5-fold, 12-fold and 24-fold respectively of its clinical dosage in humans. These findings may provid a rational basis for human health risk assessment of hUC-MSCs.